KEARIFAN LOKAL MASYARAKAT DUSUN I DAN II DESA NUSAPATI DALAM PENGELOLAAN HUTAN MANGROVE - Fahrozi, Chairul; Zainal, Sofyan; Husni, Harnani (Universitas Tanjungpura, 2017)
The increasing of deforestation cause community awareness to sustain the forest especially in Nusapati Village, through local wisdom. It can prevent the occurrence of violations that contribute to deforestation. Therefore, the purpose of study was to know the characteristics of the society (age, education, occupation, gender, and religion) and the role of local wisdom in the management of mangrove forests in hamlets I and II of the Nusapati Village. This study was conducted for 2 weeks. The method in this study was the survey. The determination of sample used the purposive sampling with interview technique. The data were analyzed with descriptive qualitative. The results showed that the management of mangrove forests by Nusapati community did not apply unwritten rules but apply a written rules as local wisdom. An unwritten rules in the Nusapati community included the Tolak Bala rituals and habits such as a decision making to be discussed, so it could solve the problems. Keyword: Local Wisdom, Mangrove Forest, Society.